Consensus on biomarkers for neuroendocrine tumour disease. Issue 9 (September 2015) - Oberg, Kjell; Modlin, Irvin M; De Herder, Wouter; Pavel, Marianne; Klimstra, David; Frilling, Andrea; Metz, David C; Heaney, Anthony; Kwekkeboom, Dik; Strosberg, Jonathan; Meyer, Timothy; Moss, Steven F; et al.
Summary: Management of neuroendocrine neoplasia represents a clinical challenge because of its late presentation, lack of treatment options, and limitations in present imaging modalities and biomarkers to guide management. Monoanalyte biomarkers have poor sensitivity, specificity, and predictive ability. A National Cancer Institute summit, held in 2007, on neuroendocrine tumours noted biomarker limitations to be a crucial unmet need in the management of neuroendocrine tumours. A multinational consensus meeting of multidisciplinary experts in neuroendocrine tumours assessed the use of current biomarkers and defined the perquisites for novel biomarkers via the Delphi method. Consensus (at >75%) was achieved for 88 (82%) of 107 assessment questions. The panel concluded that circulating multianalyte biomarkers provide the highest sensitivity and specificity necessary for minimum disease detection and that this type of biomarker had sufficient information to predict treatment effectiveness and prognosis. The panel also concluded that no monoanalyte biomarker of neuroendocrine tumours has yet fulfilled these criteria and there is insufficient information to support the clinical use of miRNA or circulating tumour cells as useful prognostic markers for this disease. The panel considered that trials measuring multianalytes (eg, neuroendocrine gene transcripts) should also identify how such information can optimise the management of patients with neuroendocrine tumours.